Pseudanthias emma new species, with notes on a collection of anthiadine serranid fishes from off Myanmar (eastern Indian Ocean) - Gill, Anthony C.; Psomadakis, Peter N. (Zootaxa, 2018)
Recent exploratory trawling off the coast of Myanmar by the R/V Dr Fridtjof Nansen has resulted in the collection of six species of anthiadine serranid fishes. Four of the species are represented by specimen vouchers: Pseudanthias emma sp. nov., P. gibbosus (Klunzinger), Odontanthias rhodopeplus (Günther) and Plectranthias sp. 1. The remaining two species are represented only by photographs: Plectranthias sp. 2 and Sacura sanguinea Motomura, Yoshida & Vilasri. Pseudanthias emma is described from the 107 mm SL holotype. It is distinguished from congeners in having the following combination of characters: dorsal rays X,16; pectoral rays 18; lateral-line scales 42; third dorsal-fin spine longest, prolonged; no papillae on posterior margin of orbit; soft part of dorsal with low scaly sheath; subopercle and interopercle indistinctly serrated; caudal fin weakly concave centrally, with elongate filaments extending from second to uppermost and second to lowermost branched rays. Plectranthias sp. 1 is a probable new species closely allied to P. sagamiensis (Katayama), from which it appears to differ in having fewer segmented dorsal rays and fewer rows of cheek scales. Plectranthias sp. 2 is a probable new species closely allied to P. alcocki Bineesh, Akhilesh, Gopalakrishnan & Jena, from which it appears to differ in lacking a large black spot on the operculum and dusky ventral spot on the abdomen. New character, habitat and distribution information is provided for all six species. Pseudanthias vizagensis Krishna, Rao & Venu is suggested as a probable junior synonym of P. pillai Heemstra & Akhilesh.